2020
DOI: 10.1017/jfm.2020.725
|View full text |Cite
|
Sign up to set email alerts
|

Using machine learning to detect the turbulent region in flow past a circular cylinder

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…With the recent developments in machine learning (ML) methods and their successful application to classical engineering problems, various advances have been made to accelerate numerical methods (Kachrimanis, Karamyan, & Malamataris 2003;Ariana, Vaferi, & Karimi 2015;Benvenuti, Kloss, & Pirker 2016;Chaurasia & Nikkam 2017;Liang et al 2018a,b;Figueiredo et al 2019;Brevis, Muga, & van der Zee 2020;Prieto 2020). This capacity has also been extended to problems related to fluid dynamics and granular flow (Radl & Sundaresan 2014;Kutz 2017;Wan & Sapsis 2018;Fukami, Fukagata & Taira 2019;Li et al 2020a;Park & Choi 2020;Aghaei Jouybari et al 2021) where its applications towards the former has been extensively reviewed (Brenner, Eldredge, & Freund 2019;Brunton, Noack, & Koumoutsakos 2020;Fukami, Fukagata, & Taira 2020a). For example, a ML approach was used for the estimation of gravitational solid flows (Garbaa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With the recent developments in machine learning (ML) methods and their successful application to classical engineering problems, various advances have been made to accelerate numerical methods (Kachrimanis, Karamyan, & Malamataris 2003;Ariana, Vaferi, & Karimi 2015;Benvenuti, Kloss, & Pirker 2016;Chaurasia & Nikkam 2017;Liang et al 2018a,b;Figueiredo et al 2019;Brevis, Muga, & van der Zee 2020;Prieto 2020). This capacity has also been extended to problems related to fluid dynamics and granular flow (Radl & Sundaresan 2014;Kutz 2017;Wan & Sapsis 2018;Fukami, Fukagata & Taira 2019;Li et al 2020a;Park & Choi 2020;Aghaei Jouybari et al 2021) where its applications towards the former has been extensively reviewed (Brenner, Eldredge, & Freund 2019;Brunton, Noack, & Koumoutsakos 2020;Fukami, Fukagata, & Taira 2020a). For example, a ML approach was used for the estimation of gravitational solid flows (Garbaa et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies by Colvert et al [15] and Alsalman et al [16] showed that ANNs and clustering techniques could be used to successfully identify types of turbulent structures based on limited data in airfoil wakes. Li et al [17] used a machine learning technique known as extreme gradient boosting to identify the region of a wake where turbulence is present and showed that these techniques were more generally applicable than ad-hoc determinations. Given such success, this raises the question as to how capably machine learning techniques can distinguish between turbulence produced by different sources, such as wakes, jets, overturning convection, shear, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the fluid prediction field, data-driven methods have been rapidly developed due to the generation of large amounts fluid data and the advancements in computer technology. In the early stage of research on flow field predictions, studies focused on predicting the airfoil and flow field around a cylinder and the application of different flow fields was studied later [26][27][28][29][30][31]. The author used a convolutional neural network (CNN) to predict the flow field around a cylinder and analyzed the difference between the CFD and predicted values from the vortex or velocity vector and vortex length perspectives [32].…”
Section: Introductionmentioning
confidence: 99%